2005
DOI: 10.1002/art.21296
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cartilage loss on magnetic resonance imaging and radiographic progression in men and women with knee osteoarthritis

Abstract: Objective. To determine the relationship between radiographic progression of joint space narrowing and cartilage loss on magnetic resonance imaging (MRI) in patients with symptomatic knee osteoarthritis (OA), and to investigate the location of MRI-based cartilage loss in the knee and its relation to radiographic progression.Methods. Two hundred twenty-four men and women (mean age 66 years) were studied. Radiographs and MRI of the more symptomatic knee were obtained at baseline and at 15-and 30-month followup. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(175 citation statements)
references
References 18 publications
8
163
2
2
Order By: Relevance
“…Although the fully extended AP weightbearing radiograph is probably no longer acceptable as a single modality for evaluating joint space loss, our use of lateral radiographs to evaluate the tibiofemoral joint space has recently been validated compared with fluoroscopy and also correlates with MRI-based cartilage loss (19). The majority of joint space loss in our cohort was seen on both the lateral and AP views.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fully extended AP weightbearing radiograph is probably no longer acceptable as a single modality for evaluating joint space loss, our use of lateral radiographs to evaluate the tibiofemoral joint space has recently been validated compared with fluoroscopy and also correlates with MRI-based cartilage loss (19). The majority of joint space loss in our cohort was seen on both the lateral and AP views.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that joint space loss is related to cartilage loss (19). We defined the knee as having had joint space loss when there was a 1-grade change (e.g., 0 -1 or 1-2) on either the lateral view or the AP view in the tibiofemoral joint from baseline to followup.…”
Section: Methodsmentioning
confidence: 99%
“…In another sample of 224 women and men with symptomatic knee OA, Amin et al (224) reported a longitudinal increase in semiquantitative MRI cartilage grading scores to be significantly associated with (semiquantitatively graded) JSN of weight-bearing femorotibial radiographs. However, progression of cartilage lesions was observed in a substantial portion of knees (42%) in which no radiographic change was apparent.…”
Section: Comparative Studies Of Quantitative Mri and Radiography In Oamentioning
confidence: 99%
“…The most likely explanation for all of these findings is that the medial joint compartment is more severely affected by OA than the lateral compartment in this model. This probably relates to biomechanical factors, since the medial joint compartment receives a greater load than the lateral compartment in most species [13,14]. In cynomolgus monkeys, the medial joint compartment precedes the lateral compartment in the development of OA lesions, possibly due at least in part to these differences in joint loading [15].…”
Section: Discussionmentioning
confidence: 99%